Efeito do pré-condicionamento físico na hipertensão induzida pela dexametasona: papel do sistema renina angiotensina - Prazeres, Paula Bessi Constantino (Universidade Federal de São Carlos, 2014)
Dexamethasone (DEX) is widely used to treat inflammation and allergies, but its chronic use determines several side effects such as hyperglycemia, muscle atrophy and hypertension (H). The renin-angiotensin system (RAS) is an important regulator of blood pressure (BP) and its increased activity may be one possible mechanism responsible to increase BP induced by DEX. On the other hand, low to moderate aerobic exercise has been recommended for treatment of hypertension and its effects on RAS have been demonstrated. We recently demonstrated that physical preconditioning attenuates H induced by DEX, however little is known about the mechanisms responsible for this response. Therefore, the aim of this study was to investigate whether RAS participated in the BP increase induced by DEX and BP reduction induced by aerobic preconditioning was associated with an alteration of RAS components. Rats were subjected to an aerobic exercise protocol on the treadmill or kept sedentary for 8 weeks. Additionally, animals were treated with DEX (1.0mg/kg of body weight per day i.p. for 10 days) and treated or not with losartan. Groups were: sedentary control (SC), DEX sedentary (SD), trained control (TC) and trained DEX (TD), sedentary losartan (SCL), sedentary DEX and losartan (SDL), trained losartan (TCL) and trained DEX and losartan (TDL). Body weight (BW), fasting glucose and resting blood pressure were analyzed. After euthanasia, the tibialis anterior (TA), soleus (SOL), flexor hallucis longus (FHL) and left ventricle (LV) were collected for evaluation of gene expression and protein levels of RAS components. Treatment with DEX caused decrease of BW and TA and FHL muscle weight (MW), and determined an increase in fasting glucose (+132%) and BP (16%). Losartan treated animals did not present BP attenuation after DEX treatment. Physical training did not prevent BW or MW loss, however it attenuated the increase in fasting glucose (60%) and BP (7%). Training increased ACE and AT1 mRNA which were further reduced in the LV muscle of TD group. Also, training increased 31% (TC) and 47% (TD) the protein levels of AGT. In the TA muscle, DEX increased by 270% the AT1 mRNA and by 175 % the MAS mRNA. TD group showed increases on AT2 mRNA (+142%) and MAS (+78%). DEX also reduced AT2 (-5%) protein levels and training did not prevent this reduction (- 13%, TD). In the SOL muscle DEX increased 87% AGT gene expression and trained rats presented an increase of AT1 (+32%) and ACE (+50%) mRNA. TD group presented increases of ACE (+53%), AT1 (+51%) and AGT (+155%) gene expression and no changes on protein levels were observed. In FHL muscle DEX determined protein level reduction of vasodilators RAS components (-20 % AT2; -33% ACE2 and - 36% MAS), although the TC group also presented a reduction on ACE2 (-16%) and MAS (-27%). TD group presented an increase of 47% on ACE2 protein level. Taken together these and the no effect of losartan on BP, we can suggest that RAS is not the main mechanism involved in this model of Hypertension induced by DEX.
Keywords: Glicocorticóides; Exercícios físicos; Pressão arterial; Angiotensina II; Glucocorticoids; Exercise; Blood pressure; Angiotensin II; CIENCIAS BIOLOGICAS::FISIOLOGIA